Correlation of total leukocyte count and platelets with the recovery phase in children with dengue admitted in an urban tertiary care center - Kotwal, Nishikant; Mandlik, Milind; Daharwal, Sachin; Taposhi, Kamble; Madhura, Abhishek; Ughade, Suresh (Indian Journal of Child Health, 2019)
Introduction: Dengue ranks among the most significant mosquito-borne viral diseases in the world. Anticipatory management and monitoring indicators are essential in effectively administering therapies in the critical phase. Only a few studies have explored and documented the relationship between laboratory parameters and convalescing children with dengue. Objectives: The objective of the study was to delineate correlation of total leukocyte count (TLC) and the onset of convalescence (recovery) phase in children with dengue, and second, to determine the correlation of platelet count and TLC with the duration of hospital stay. Materials and Methods: This prospective observational study was conducted in a tertiary care hospital in Nagpur from July 2018 to November 2018 when the dengue outbreak in the city and the vicinity of this central India region was at its peak. The inclusion criteria consisted of children of 1–18 years of age from either sex, fever of recent duration, and serological positivity for dengue (NS1 antigen and/or IgM and IgG antibody positivity) were included in the study. The exclusion criteria were febrile illness other than dengue, comorbid conditions such as HIV, bronchial asthma, congenital heart disease, and complicated dengue cases. Results: Out of 190 cases, 65.8% were males, the average duration of fever at the time of admission being 4.9±2.2 days (Range 2–10 days). The average duration of illness was 10.1±2.4 days (range 4–19 days). Eleven (5.79%) subjects had third spacing (capillary leak). The average TLC recovery time was 8.45±1.57 days (7–12days) from the onset of illness, while the mean capillary leak recovery time was 9.45±1.57 days (8–11days). A negative correlation was observed from a 2nd – day hospital stay with both TLC and platelets in patients with the capillary leak. Conclusion: In resource-limited settings, pediatricians can utilize TLC in predicting recovery, and thus can reduce the treatment costs.